MODELING INFILTRATION KINETICS OF LIQUIDS INTO POROUS ALUMINA PREFORMS - Posman Manurung; It Meng Low; Craig Buckley (Jurnal Sains Materi Indonesia, 2006)
MODELING INFILTRATION KINETICS OF LIQUIDS INTO POROUS ALUMINA PREFORMS. Alpha-alumina preform was infiltrated with different infiltrant and pressure for studying the infiltration kinetic. Effects of pre-sintering temperature, type of infiltrant, pressure and multiple infiltrations on the rate of infiltration into porous alumina preforms were described. The pore radius of alumina preform is calculated based on the preform water system by using Washburn model. The pore radius from this model, r of 0.0147 μm is good agreement to the average pore radius found by using mercury porosity measurement, r of 0.0170 μm. The pore radius of 0.0147 μm is used to calculate the rate of infiltration, k. The k factors are 64.83 x 10-5 ms½ and 27.11 x 10-5 ms½ for water and TiCl3 respectively without involving pressure in the calculation. On the other hand, by using pressure, the k factors are 75.14 x 10-5 ms½ and 31.40 x 10-5 ms½ for water and TiCl3 respectively. Other formulas were also included as comparisons. The kinetic of water and titanium trichloride alumina preform system is parabolic in time or linier in square root of time.